ANALISA TINGKAT AKURASI PENGUKURAN BACKLASH PADA SPUR GEAR MENGGUNAKAN VARIASI METODE - Rivandra Rezani; Azhis Sholeh Buchori (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
Mechanical Basic Maintenance and Repair Practices is one of the practical courses in the Machinery Maintenance study program, which is studying the backlash measurement of gears, especially the spur gear on a lathe where the backlash is a gap between two interrelated gears. Based on the student’s practice when doing backlash measurements, there were obstacles that the feeler gauge used as a tool to measure the backlash was too large,  it was unable to reach the backlash of the gears on a small lathe. The research method used is by measuring the backlash on the spur gear using a thickness gauge of 0.01 mm accuracy and 0.01 mm accuracy of dial  indicator. Both methods are compared in order to obtain data on measurement methods with more accurate results and to get data that with the advantages and disadvantages of each measurement method which is used as a guide as well as recommendations for students in measuring backlash gears especially on spur gear. The results showed that the backlash measurement method using a thickness gauge had higher measurement accuracy and a more practical measurement method than using a dial indicator. Keywords: Backlash, Measurement, Spur Gear